A novel spectral technique for 2D fractional telegraph equation models with spatial variable coefficients. Issue 1 (31st December 2022) - Ahmed, Hoda F.; Hashem, W. A.
Abstract : In this paper, a class of the two-dimensional (2D) mathematical models of the time fractional telegraph equation with spatial variable coefficients is considered. These models include the 2D time fractional telegraph equation (2D-TFTE), the 2D time fractional diffusion wave equation with damping (2D-TFDWED) and the 2D time fractional wave equation (2D-TFWE). The fractional derivatives are described in the Caputo sense. A novel spectral technique is used to solve the aforementioned models. The technique is based on the operational matrices of the shifted Gegenbauer polynomials in conjunction with the spectral tau method. The product of operational matrices of the space vectors is constructed in a simple way to remove the obstacle that facing the use of the tau method in solving the variable coefficients fractional/integer order PDEs. Miscellaneous numerical experiments are offered to verify the accuracy and rapid rate of convergence of the presented numerical technique.